A Systematic Review of Autobiographical Memory and Mental Health Research on Refugees and Asylum Seekers - Khan, Sanjida; Kuhn, Sara K.; Haque, Shamsul (Frontiers in Psychiatry, 2021)
Research examining trauma, memory, and mental health among refugee and asylum-seeking people has increased in recent years. We systematically reviewed empirical work focusing on the link between autobiographical memory and mental health among these populations. The review protocol was registered with PROSPERO (CRD42018095888). Six major databases were searched in August-2020 with no time limit for publication. Following PRISMA Statement guidelines, 22 articles reporting ten quantitative, nine qualitative, and three mixed-method studies were selected from 254 articles identified in the initial search. A basic convergent and qualitative meta-integration technique was employed for data extraction. Four recurrent themes were extracted: (1) memory activation method, (2) memory features, (3) memory content, and (4) refugee mental health. Theme 1 illustrates that narrative interviews, important event recall, and cue word methods were used in most studies. Theme 2 highlights that memories of refugee people were often less specific, inconsistent, and negative-focused. Retrieval failure was also common among these people. Theme 3 reveals that refugee and asylum-seeking people frequently discussed their abandoned identities, lost resources, injustices, ongoing sufferings, and pointless futures. Finally, theme 4 identifies the prevalence of various mental health conditions like Posttraumatic Stress Disorder, depression, helplessness, and anger among these people. The results are discussed in the context of the current autobiographical memory and mental health theories, considering refugee-specific experiences in the asylum process and refugee status.